Oceanic states of consciousness—an existential-neuroscience perspective - Unterrainer, Human-Friedrich (Frontiers in Human Neuroscience, 2025)
Oceanic states of consciousness—characterized by ego dissolution, unity, and timelessness—have long occupied a liminal space between psychopathology and transcendence. This paper explores these states through the interdisciplinary lens of existential neuroscience, integrating insights from psychoanalysis, existentialism, affective neuroscience, and psychedelic research. Starting with the psychoanalytic tension between Freud’s view of the oceanic feeling as a regressive illusion and Jung’s framing of it as a transformative encounter with the unconscious, this paper examines how creative and mystical experiences often arise from this dissolution of self-boundaries. Drawing on art theorist Anton Ehrenzweig and examples from figures like Vincent van Gogh and Antonin Artaud, I highlight how oceanic states may catalyze both visionary insight and psychological disintegration. Neuroscientific models, including the REBUS theory and studies of the Default Mode Network (DMN), suggest that ego dissolution reflects a flexible reorganization of brain function rather than dysfunction. The Peri-Aqueductal Gray (PAG), a midbrain structure associated with affect regulation and spiritual experience, emerges as a key neural hub linking primal affective states with mystical awareness. Existential thinkers such as Sartre, Heidegger, and Merleau-Ponty provide a philosophical framework for interpreting these phenomena as moments of existential rupture and potential authenticity. Oceanic states thus challenge conventional notions of the self as fixed and bounded. Rather than categorizing them as pathological or purely mystical, it is proposed here that these states represent affectively charged boundary experiences - ones that require contextual integration and offer deep insight into the nature of selfhood, meaning, and transformation.